The influence of laser-microgrooved implant and abutment surfaces on mean crestal bone levels and peri-implant soft tissue healing: a 3-year longitudinal randomized controlled clinical trial - Assma Syed Ahamed; P. S. G. Prakash; Jasmine Crena; Dhayanand John Victor; Sangeetha Subramanian; Devapriya Appukuttan (SpringerOpen, 2021)
Abstract Purpose The study aimed to compare clinical and radiographic parameters of peri-implant site of laser-microgrooved implants with either laser-microgrooved or regular machined prosthetic abutment post 3 years of early loading. Method Twenty edentulous sites of systemically and periodontally healthy individuals were allocated into two groups in this prospective, two-armed, randomized double-blinded clinical trial in 1:1 ratio, wherein each site received laser-microgrooved implants with either laser-microgrooved or machined prosthetic abutments. Outcome measures included full-mouth plaque (FMPS%) and bleeding score (FMBS%), site-specific plaque (SPS%) and bleeding score (SBS%), peri-implant sulcus depth (PISD mm), and mean crestal bone loss (MCBL mm) evaluated at baseline (6 weeks), 1 and 3 years post-early loading. Mean and standard deviation of all parameters were estimated, between groups and at different time points using independent and paired t-test, respectively, Normality was checked using Kolmogorov-Smirnov test and Shapiro-Wilk test, P value ≤ 0.05 was considered as statistically significant. Results Three-year follow-up of test group showed statistically significant reduction in SPS, SBS, PISD (P value ≤ 0.001). The MCBL reduced from 1.93 mm to 0.61 mm (P value ≤ 0.001); in other words, a bone gain of 0.15 mm was obtained in the test group. Conclusion Within the limitations of the present study, laser-microgrooved implants loaded with laser-microgrooved prosthetic abutments showed superior results clinically and radiographically when compared to loading with machined abutments.